Pengaruh Harga dan Kelengkapan Produk terhadap Keputusan Pembelian pada Aplikasi Shopee di Kota Mataram - Tri Mei Elita (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine the variables that influence the purchasing decisions of Shopee application users. The variables are price and product completeness. The sample in this study was obtained using purposive sampling method in the city of Mataram who had made a purchase at Shopee. Based on the selection that has been made, 65 respondents were taken to be the sample in this study. The data collection method used in this study was a questionnaire. The analysis used includes data instrument test, validity test, multiple linear regression analysis, classical assumption test (multicollinearity test, normality test, heteroscedasticity test), and hypothesis testing (t test) from the analysis it is concluded that price has a significant effect on purchasing decisions and product completeness does not have a significant effect on purchasing decisions.